(untitled) - Leskovec, Jurij (Cambridge, 2014)
This book focuses on practical algorithms that have been used to solve key problems in data mining and which can be used on even the largest datasets. It begins with a discussion of the map-reduce framework, an important tool for parallelizing algorithms automatically.
Khai thác dữ liệu lớn
Keywords: Data mining,Knowledge management,Khai thác dữ liệu,Quản trị tri thức; Congresses,Congresses,Hội nghị,Hội nghị